Narrativas da professora Ruth Cavalcante: lições de educação, de militância e de exílio no período 1960 a 1980 - Ricarte, Erbênia Maria Girão (2018)
This research offers a sociohistorical analysis of the educational, political and intellectual trajectory of Professor Ruth Cavalcante, through her memories, centered on the period from the 1960s to the 1980s. time that corresponds to its exit from the central interior of Ceará to the capital Fortaleza to study, until its exile in Germany and return to Brazil. It aims to produce the biographical record of the life trajectory and performance of Professor Ruth Cavalcante, considering the historical period in which the era of the Military Regime in Brazil lived until her return from exile, explaining in a contextualized way the life history of the teacher and cultural mediator from the verbal and visual narratives resulting from the dialogues / interviews between teachers (researched and researched) in which the biography recalls the main moments of her life between formation, militancy and exile. The dissertation is based on the concepts of history, memory, trajectory, biography, education and intellectual mediation: the concept of history, proposed by Le Goff, the notion of memory proposed by Paul Ricoeur, the considerations of life trajectories thought from the researcher Rosenthal, in the understanding in biography argued by Delory-Momberger, Education from the legacy of Paulo Freire with approaches in Carlos Brandão and Maurice Tardiff regarding the history of education and in the concept of intellectual mediator discovered in the readings of Ângela Gomes and Patricia Hansen, allowed to see such actions in addition to a history, but as cultural and intellectual mediation of the biography from the sense that the intellectual mediator brings the groups closer to cultural assets. It is a historical-biographical, longitudinal and qualitative-ethnographic research, with the use of written, oral and imaginary sources, through field research. We will resort to the oral methodological resource, through semi-structured interviews recorded with Professor Ruth, in addition to the visits in the municipality of Pedra Branca and other secondary sources. By intertwining the intellectual, the political-intellectual trajectory, her contacts in the field and in militancy, we find ways to understand and interpret the critical and mediating stance of Professor Ruth Cavalcante in face of society and all the challenges of the time. The research intends to contribute, from the analysis of the trajectory of a militant teacher, to a better understanding of the dynamics of the political activism, education and intellectual mediation of Ceará from Ruth's involvement with other spheres and social groups.